ASSESSMENT OF IMMUNITY INDUCED BY NEWCASTLE DISEASE VIRUS VACCINES AND DETERMINE THE BEST VACCINATION PROGRAM IN BROILER CHICKEN - Douaa Y. Talib; Hazim T. Thwiny (Basrah Journal of Veterinary Research)
The objectives of current research were evaluate the efficacy of commercially availableNewcastle disease vaccine and determine the best vaccination program. A total number of 150one-day-old unvaccinated chicks were divided equally into 5 groups. One vaccination programwere used for each group which differ from each other while group 5 was unvaccinated controlgroup. Serum were collected from all groups and five chickens from each group were sacrificed.Afterward immunization HI geometric mean titer (GMT) rates were observed that bothseroconverted birds in Group 1 to Group 4 have risen statistically significantly, with statisticalsignificant changes. (p < 0.05). However, the birds in group 4 which had the best HI titers(147). The levels of ChIFN-γ was measured by ELISA, there were also higher in the vaccinatedgroups (group 1, 2, 3 and 4) than in the non-vaccinated group. Group 4 also had the best ChIFN-γ level. The higher values of lymphoid organs (spleen, Bursa of Fabricius and thymus) indiceswere in vaccinated groups are compared to non-vaccinated groups, while between vaccinatedgroups there was no significant different (P < 0.05). Commercial ND vaccines are effective andvaccination scheme of group 4 (live ND vaccine at 7th day of age by eye drop as primaryvaccine followed by live ND vaccine at 21st day of age by drinking water as booster dose) hasmore protective effects in broiler chicken.